ECTOPARASITES IN CULTIVATED BUJURQUI (CICHLASOMA AMAZONARUM; PISCES: CICHLIDAE) REARED IN FISH PONDS - Lo P., Juan (2011)
The aim of the present study was to identify ectoparasites and to establish the frequencies of infections in Cichlasoma amazonarum (Pisces: Cichlidae) raised in artificial ponds in Iquitos, Peru from October to December 2004. Ectoparasites collected from the skin and gills in 225 fish were stained using Delafield Hematoxiline. The frequency of ectoparasites was 78.0 ± 6.1% monogeneans and 0.9% maxillopoda (Crustacea: Branchiura). Among monogenean infections, 88.1% corresponded to parasites of Dactylofyridae family and 6.2% of Gyrodactylidae family, whereas 5.7% to mixed infections of both families. All maxillopoda found were Dolops geayi. One to three parasites per individual were found in 80.2% of the sampled fish, indicating of low parasite burden, which may no affect fish health. There was no significant correlation between biometric measurements and monogeneans infection in C. amazonarum. This study could indicate that monogeneans in Peruvian Amazon cichlids are common.